A survey on architectures, protocols, applications, and management in wireless sensor networks - Kalantary, Samira; Taghipour, Sara (Journal of Advanced Computer Science & Technology, 2014)
With the recent technological advances in wireless communications, integrated digital circuits, and micro electro mechanical systems (MEMS); development of wireless sensor networks has been enabled and become dramatically feasible. Wireless sensor networks (WSNs) are large networks made of a numerous number of sensor nodes with sensing, computation, and wireless communications capabilities. Many various routing, power management, and data dissemination protocols have been designed for wireless sensor networks (WSNs) dependent on both the network architecture and the applications that it is designed for. In this paper, we present the state of the art of wireless sensor networks’ architecture and design features. Also, in this paper, we introduce recent work on routing protocols for WSNs and their design goals and challenges. Also, an overview of the application that WSNs assist in is presented. Finally, several open research questions of wireless sensor networks management and issues are suggested and put forward. Keywords: application, architecture, management, protocol, wireless sensor network.